An audit of the management of nicotine withdrawal in an Australian inpatient unit: are we there yet?. (February 2018) - Iyer, Reena; Smith, David; Lawn, Sharon
Objectives: This paper reports outcomes of a clinical audit of smoke-free policy implementation within an Australian inpatient psychiatric setting. It aimed to evaluate assessment of smoking status and subsequent management of nicotine withdrawal, and investigate any patient factors influencing these processes. Methods: A total of 67 medical case notes were retrospectively analysed for inpatients admitted to psychiatric units of a general hospital in South Australia, from July to September 2015. Patient demographic variables and information from the hospital's Smoking Assessment and Management Form (SAMF) were recorded. Data analysis involved descriptive statistics and Chi-square tests of association between dependent variables (how the SAMF was completed) and independent variables (sex, voluntary status, diagnosis). Results: The SAMF was implemented for most patients (76.1%), with 64.71% completed within 24 hours of admission; though, many were incomplete. Nicotine dependence was not properly assessed for 42.3% of smokers; 69.23% were prescribed nicotine replacement therapy (NRT), despite most scoring moderate to high nicotine dependence. No statistically significant relationships were found between patient factors and form completion. Conclusions: SAMF completion was timely for most patients; however, sections important for determining support actions remained largely incomplete, suggesting patients' nicotine withdrawal is not being adequately addressed. More work is needed to improve inpatient staff's assessment to ensure optimal care.